Cylindrical Gravastar Like-Structures in f(G) Gravity - M. Z. Bhatti; Z. Yousaf; A. Rehman (Galaxies, 2022)
The aim of this manuscript is to explore singularity-free solution for a specific self-gravitating highly dense object known as gravastar suggested by Mazur and Mottola, in the context of <semantics>f(G)</semantics> gravity theory. Gravastars are regarded as a possible alternate to black hole. To derive modified field equations and law of conservation related to Gauss-Bonnet gravity, we assume cylindrically symmetric irrotational configuration. Particular equation of states are used for the illustration of three sectors of gravastar model. Furthermore, we are intended to obtain a regular solution for our model and graphs will be used to elaborate various substantial characteristics of it.